Effectiveness of Functional Electrical Stimulation Versus Spencer Technique in Patients with Adhesive Capsulitis - Zia, Shaista; Babur, Muhammad Naveed; Sarwar, Rukhshanda; Zaheer, Gulnaz; Irshad, Asima (Medical Journal of South Punjab, 2024)
Objective: To compare functional electrical stimulation with spencer approach for relieving pain, stiffness and enhance range of motion and functional capacity among adhesive capsulitis subjects. Methodology: Study design was randomized control trial. Johar Pain Relief Center and Ali Fatima hospital Lahore were study setting. Sample size was 32. Study ran Sep 2023 to May 2024. Both gender from 40 to 60 years having diabetic frozen shoulder and stiff shoulder for at least 3 months were included. Having dislocated shoulder, fracture within past 12 weeks excluded. Ethical considerations were followed throughout study. 2 intervention groups were made: group B undergone spencer technique or group A received functional electrical stimulation. Data was gathered using Goniometer, VAS and shoulder pain and disability index. SPSS version 25 utilized for statistical analysis. Results: Group B (spencer technique group) showed more improvement post-intervention VAS scores and mean difference was 1.222 with p-value .002. SPADI pain scores were with mean difference 6.055 having p-value .006 and ROM were also improved with p value <.001 indicating a significant difference post-intervention but adduction showed no improvement pre and post value. Conclusion: Both spencer technique and functional electrical stimulation hold promise as effective interventions for improving pain ,ROM and shoulder disability but spencer technique showed more significant results as compare to functional electrical stimulation.